2022
DOI: 10.3389/fonc.2022.948662
|View full text |Cite
|
Sign up to set email alerts
|

Machine learning prediction of prostate cancer from transrectal ultrasound video clips

Abstract: ObjectiveTo build a machine learning (ML) prediction model for prostate cancer (PCa) from transrectal ultrasound video clips of the whole prostate gland, diagnostic performance was compared with magnetic resonance imaging (MRI).MethodsWe systematically collated data from 501 patients—276 with prostate cancer and 225 with benign lesions. From a final selection of 231 patients (118 with prostate cancer and 113 with benign lesions), we randomly chose 170 for the purpose of training and validating a machine learni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 33 publications
(29 reference statements)
0
3
0
Order By: Relevance
“…Wang conducted a machine-learning prediction study of prostate cancer, using transmittal ultrasound video clips, and found that the AUCs of the SVM model in the validation set and test set were 0.78 and 0.75, respectively, and the diagnostic efficiency of the SVM model was higher than that of MRA-based diagnosis (AUC was 0.78 vs. 0.65/0.75 and 0.75 vs. 0.65/0.72, respectively). Li found that the MRI-based SVM model had high diagnostic efficiency and stability ( 46 ). In this study, the accuracy of the SVM model for the diagnosis of clinically significant prostate cancer was 95%, and the AUC was 0.845, which is similar to the effect in Li’s study.…”
Section: Discussionmentioning
confidence: 99%
“…Wang conducted a machine-learning prediction study of prostate cancer, using transmittal ultrasound video clips, and found that the AUCs of the SVM model in the validation set and test set were 0.78 and 0.75, respectively, and the diagnostic efficiency of the SVM model was higher than that of MRA-based diagnosis (AUC was 0.78 vs. 0.65/0.75 and 0.75 vs. 0.65/0.72, respectively). Li found that the MRI-based SVM model had high diagnostic efficiency and stability ( 46 ). In this study, the accuracy of the SVM model for the diagnosis of clinically significant prostate cancer was 95%, and the AUC was 0.845, which is similar to the effect in Li’s study.…”
Section: Discussionmentioning
confidence: 99%
“…used a machine learning-based method to extract features from TRUS video clips to predict csPCa and achieved an AUC of 0.78. 41 However, these approaches required time-consuming manual preparation, which may not be suitable for routine clinical use. Our method requires the least amount of manual pre-processing and may be more advantageous for practical applications.…”
Section: Discussionmentioning
confidence: 99%
“…The ML-based imaging radiomics transforms visual image information into in-depth quantitative indicators, extracts a large amount of image feature information from medical images, and constructs predictive models based on feature information ( 16 , 17 ). In our previous study, prostate features were extracted from TRUS videos, and the SVM model constructed using ML algorithms was found to outperform MRI-based advanced radiologist diagnosis for PCa (AUC = 0.78 vs. 0.75 in the validation set and 0.75 vs. 0.72 in the test set) ( 18 ). Techniques such as quantitative MRI analysis and computer-aided diagnosis have expanded the scope to analyze prostate MRI, and have been shown to improve diagnostic accuracy and reproducibility ( 19 21 ) and reduce inter-diagnostician variability by highlighting suspicious areas on MRI ( 22 ).…”
Section: Discussionmentioning
confidence: 99%